Intensification of no‐till agricultural systems: An opportunity for carbon sequestration. Issue 5 (5th August 2021) - Nicoloso, Rodrigo S.; Rice, Charles W.
Abstract: The "4 per 1, 000" initiative was launched at the 21st Conference of the Parties (COP21) stimulating a long‐standing debate on the potential of no‐till (NT) to promote soil C sequestration. Previous reviews found little or no soil organic C (SOC) accrual in NT soils as compared with full inversion tillage when soils are sampled deeper than 30 cm. Here, we present the results of a global meta‐analysis of studies assessing SOC and total N (TN) storage and dynamics in NT and tilled soils from the most important agricultural regions of the world. Overall, our results show that NT soils stored 6.7 ± 1.9 Mg C ha –1 and 1.1 ± 0.4 Mg N ha –1 more than tilled soils (0‐to‐100‐cm depth) with an average of 16 yr of NT, in contrast with previous findings. However, C sequestration (+4.7 ± 1.9 Mg C ha –1 in the 0‐to‐60‐cm depth with an average of 11 yr of NT) depended on the association of NT with increased crop frequency and the inclusion of legumes cover crops. Single‐cropping systems lack the necessary C inputs to offset SOC losses in the soil profile (below 30‐cm depth). However, double‐cropping systems decreased soil TN that may constrain future C sequestration. The use of legumes alleviated TN loss and supported soil C sequestration. Briefly, our findings indicate that NT can avoid SOC losses from tilled soils, partially offsetting CO2 emissions from agriculture. Moreover, NT with agricultural intensification can promote soil C sequestration, thus contributing to soil quality, food security, and adaptation to climate change. Core Ideas: Here, we present a meta‐analysis on deep SOC and TN storage and dynamics in tilled and NT soils. No‐till soils stored more SOC and were more conservative of TN than tilled soils. Differences in SOC stocks between tilled and NT soils increased with temperature. Carbon sequestration in NT soils increased with intensification of cropping systems. The use of legumes cover crops sustained TN stocks and promoted soil C sequestration under NT.